HUMOR AND SATIRE IN W. SHAKESPEARʼS COMEDIES - Xudoyberdiyeva Marjona Sunatillo qizi; Khamitov Eldorbek (Лучшие интеллектуальные исследования, 2024)
William Shakespeare is renowned for his ability to infuse his comedies with humor and satire, creating timeless works that continue to entertain audiences today. In his comedies, Shakespeare employed various comedic techniques, including wordplay, mistaken identity, physical comedy, and satire, to engage and amuse his audience. Wordplay played a significant role in Shakespeare's comedies, with characters engaging in witty banter, puns, and clever wordplay. For example, in "Much Ado About Nothing," Beatrice and Benedick engage in a battle of wits, exchanging sharp and humorous insults. This verbal sparring showcases Shakespeare's skill in crafting clever and humorous dialogue.